การศึกษาคุณลักษณะของนักวิจัยอันพึงประสงค์ที่ควรเสริมสร้างให้แก่นิสิตในระดับบัณฑิตศึกษา - ทองไทย, วสันต์ (Journal of Research and Curriculum Development, 2011)
บทคัดย่อไม่สมบูรณ์ The Study of Desirable Researchers' Characteristics which will be Able to Enhance Graduate Students The purpose of this research was to examine desirable researchers' characteristics which will be able to enhance graduate students in social and educational science. Population were graduate students, lecturers and graduate users. There were 400 samples chosen by stratified random sampling. Questionnaires were used to collect data by postal mail. Three hundred and twenty sets of returned questionnaires were analyzed by using frequency, percentage, chi-square and factor analysis. The research result found that there was consistency in the opinions on desirable researchers' characteristics from all sample groups. Over 70 percent of samples revealed that all desirable researchers' characteristics were needed at high level and above. Top three characteristics were mostly rated at highest level were responsibility, self-discipline and respect for others, in respective orders. The desirable researchers' characteristics can be categorized into 6 factors as follows 1) knowledge in content and research methodology 2) language ability and skills in using computer program 3) thinking ability 4) management skill 5) researcher habit and code of conduct and 6) personality.